Efficient Method for the Synthesis of Functionalized Basic Maleimides. (16th December 2013) - Salewska, Natalia; Milewska, Maria J.
<x xml:space="preserve">Abstract</x> A three‐step procedure involving Diels–Alder condensation of maleic anhydride with furane, formation of N‐substituted imide upon reaction with appropriate diamine, and a final retro Diels–Alder regeneration of the maleic carbon–carbon double bond is proposed for an unequivocal synthesis of N‐substituted basic maleimides. The novel method is characterized by mild reaction conditions, easy work‐up, high yields, and no need for additional catalysis.